Pengaruh Model Pembelajaran Numbered Heads Together dengan Strategi Worked-Example terhadap Kemampuan Penalaran Siswa - Monika Nurazizah; Cecep Anwar Hadi Firdos Santosa; Aan Subhan Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2020)
The study aims to determine the influence of Numbered Heads Together learning model with worked-example strategy for the students's mathematical reasoning skills. This method of research was quasi-exsperiment with Nonequivalent design Pretest Posttest Control Group Design. The subject in this study was the X class of MIA 2 as the experimental class and X MIA 4 as the control class.Â The instrument used is a test instrument of mathematical reasoning ability of students. Analysis of hypotheses data using t test, which is through the prerequisite test of normality and homogeneity. The results of this study, Numbered Heads Together learning model with worked-example strategy, have a better influence on reasoning ability than conventional learning models.